Load Test on Combined Pile and Cap / Pad Foundation System on Compressible Calcareous Sand and Comparison with FEM Modelling - Abram Kris Wicaksono; Petrus Chanel Suprihadi Santoso; Paulus Pramono Rahardjo (Himpunan Ahli Teknik Tanah Indonesia, 2023)
An optimum type of foundation is expected to support 2 – 3 stories residential house on reclamation area to avoid deep foundation. The foundation will sit on engineering fill that constructed with calcareous sand which is classified as compressible sand. Below that part, at the original ground medium density sand and very soft marine clay is found stratified. Typical column in the residential building will have about 100 tons load intensity and based on this project, the design load for a single pile is 32 ton. Since no additional compression on soft clay layer is expected after building construction, than combine cap/pad foundation with short pile 6.5 m length is proposed. Load test with stress cell for this combine pile and cap/pad foundation was performed. The load test result show that interpretation using Chin’s and Mazurkiewicz’s Method obtained that the combined pile and cap/pad foundation’s ultimate bearing capacity of 112 – 119 tons. Analysis using stress cell data shows that the cap/pad carry about 31.8 % of the total load. Finite element analysis with axisymmetric condition conducted to study load distribution on combine pile and cap/pad foundation system. Analysis result was show that the cap or pad can carried about 38.1% of design load during testing. The 6.3% deviation between the stress cell and FEM results could be attribute by the assumption when calculating the load acting on cap/pad foundation. The stress cell analysis used the assumption that the load carried by the cap/pad foundation was uniform while the FEM results showed a non-uniform load.